2011
DOI: 10.1080/00222348.2011.557629
|View full text |Cite
|
Sign up to set email alerts
|

Study of PEO—PPO—PEO Copolymers Conformational Changes: Viscosity and Dynamic Light Scattering Measurements

Abstract: The self-assembly behaviour of poly(ethylene oxide)-b-poly(propylene oxide)-b-poly (ethylene oxide) copolymers, (EO) 13 (PO) 30 (EO) 13 (Pluronic L64), and (EO) 70 (PO) 30 (EO) 70 (Pluronic F68) in water and in p-xylene has been elucidated by using viscosity and dynamic light scattering measurements to investigate the effects of hydrophilic chains length on their conformational changes. The viscosity measurementswere performed for a range of temperature varying from 27 • C to 60 • C and concentration from 4 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The PEO-PPO-PEO blocks become less soft that make the formation of the direct or the reverse micelles in pure p-xylene impossible. These results are in good agreement with the results obtained by Ghaouar et al [1] using DLS measurements for various concentrations of F68 and L64 dissolved in pure p-xylene at room temperature, where they have shown the nonexistence of a CMC for both Pluronics studied. An additional factor that makes the direct or the reverse micelles formation impossible in pure p-xylene is that the PPO block was much shorter than the PEO blocks for Pluronic F68 [3,12].…”
Section: Binary Mixtures Of Pluronic F68/solventsupporting
confidence: 92%
See 3 more Smart Citations
“…The PEO-PPO-PEO blocks become less soft that make the formation of the direct or the reverse micelles in pure p-xylene impossible. These results are in good agreement with the results obtained by Ghaouar et al [1] using DLS measurements for various concentrations of F68 and L64 dissolved in pure p-xylene at room temperature, where they have shown the nonexistence of a CMC for both Pluronics studied. An additional factor that makes the direct or the reverse micelles formation impossible in pure p-xylene is that the PPO block was much shorter than the PEO blocks for Pluronic F68 [3,12].…”
Section: Binary Mixtures Of Pluronic F68/solventsupporting
confidence: 92%
“…The triblocks copolymers based on poly(ethylene oxide)poly(propylene oxide)-poly(ethylene oxide), usually named Pluronics (manufactured by BASF) or Poloxamers (manufactured by ICI), are able to form direct micelles with PEO coronas and PPO cores or reverse micelles with PEO cores and PPO coronas under some conditions. The investigation of their association properties has had considerable ambiguity due to the fact that some of them are able to form direct micelles, reveres micelles, and various arrangements under several conditions, whereas some of them showed that the dimension of the structures formed was equal to the length of the hydrophobic stretched blocks [1][2][3][4][5][6][7][8][9]. In this regard, the critical micelle concentration, the critical micelle temperature, the aggregation number, and the polydispersity are usually given with a certain uncertainty [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, complete phase diagrams can be obtained for ternary compounds as described by Wang et al, Son et al, and Yuan et al [7][8][9] When a mechanical perturbation is applied (like in a mixing tank), shear stresses induce deformation of the microstructure that can lead to phase transitions. [10][11][12] One of the most popular structured fluids investigated in the literature, both via experiments and simulations, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] is composed of water and the triblock co-polymer of polyethylene oxide (PEO)-polypropylene oxide (PPO)-polyethylene oxide (PEO), under the commercial name Pluronic®, by BASF. This nonionic co-polymer can be manufactured by varying the number of EO and PO monomers such that the length of the hydrophilic (PEO) and hydrophobic (PPO) blocks can be varied to tune its amphiphilic properties, hence its phase diagram together with the temperature.…”
Section: Introductionmentioning
confidence: 99%